ANALISIS PELAKSANAAN FUNGSI PENGAWASAN INSPEKTORAT DAERAH DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH DI KABUPATEN SABU RAIJUA - Ady Cusrell William Ly; Anthon Simon Y. Kerihi; Sarlin P. Nawa Pau (Universitas Nusa Cendana, 2022)
The Office of the Regional Inspectorate of Sabu Raijua District is one of the government agencies that has a supervisory function on the implementation of regional government. Where one of the missions to be achieved is to improve the quality of supervision of the implementation of regional government. However, the problem that occurs is that the implementation of the supervisory function on the implementation of regional government in Sabu Raijua district, especially in 2019 to 2021, has been carried out according to the provisions, but there are still several sub-activities that have not been implemented. implemented due to the lack of available resources. Data collection techniques used in this research are questionnaires, interviews, and documentation. In this study, the analysis used was descriptive qualitative data analysis. The results of the study concluded that the implementation of the supervisory function, especially at the Regional Inspectorate of Sabu Raijua Regency in 2019 to 2021, namely audit, review, evaluation, and monitoring had been carried out according to the provisions, but there were several sub-activities that had not been carried out due to lack of adequate human resources and time allocation. implementation of inadequate supervisionactivities.